Dietary fat exacerbates postprandial hypothalamic inflammation involving glial fibrillary acidic protein‐positive cells and microglia in male mice. Issue 1 (13th July 2020) - Cansell, Céline; Stobbe, Katharina; Sanchez, Clara; Le Thuc, Ophélia; Mosser, Coralie‐Anne; Ben‐Fradj, Selma; Leredde, Joris; Lebeaupin, Cynthia; Debayle, Delphine; Fleuriot, Lucile; Brau, Frédéric; Devaux, Nadège; et al.
Abstract: In humans, obesity is associated with brain inflammation, glial reactivity, and immune cells infiltration. Studies in rodents have shown that glial reactivity occurs within 24 hr of high‐fat diet (HFD) consumption, long before obesity development, and takes place mainly in the hypothalamus (HT), a crucial brain structure for controlling body weight. Here, we sought to characterize the postprandial HT inflammatory response to 1, 3, and 6 hr of exposure to either a standard diet (SD) or HFD. HFD exposure increased gene expression of astrocyte and microglial markers (glial fibrillary acidic protein [GFAP] and Iba1, respectively) compared to SD‐treated mice and induced morphological modifications of microglial cells in HT. This remodeling was associated with higher expression of inflammatory genes and differential regulation of hypothalamic neuropeptides involved in energy balance regulation. DREADD and PLX5622 technologies, used to modulate GFAP‐positive or microglial cells activity, respectively, showed that both glial cell types are involved in hypothalamic postprandial inflammation, with their own specific kinetics and reactiveness to ingested foods. Thus, recurrent exacerbated postprandial inflammation in the brain might promote obesity and needs to be characterized to address this worldwide crisis. Main Points: Short‐term dietary fat exposure exacerbates post‐prandial hypothalamic inflammation and modulates hypothalamic neuropeptides gene expression that regulates energy balance. Both responses involved GFAP‐positive and microglia cells.